The effect of land consumption on municipal tax revenue: Evidence from Bavaria - Sebastian Langer; Artem Korzhenevych (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
This paper aims to quantify the municipal tax revenue effects of built-up area increases. The assumed existence of these effects is one of the key reasons for ongoing land consumption on the side of the municipalities. Some previous case studies however suggested that these effects might be not large enough especially in rural municipalities and would thus make land development not profitable. We estimate the effect of built-up industrial and commercial (BIC) area change on the business tax revenues in cross-sectional instrumental variable (IV) estimations. Based on detailed data for Bavaria, we find a significant and positive tax revenue effect of an increase in municipal BIC area. There exist strong differences in the size of this effect between urban and rural municipalities. The largest effects are generated by the BIC area in the large cities and become substantially smaller when these are dropped from the sample. Based on these findings, we reflect on the tradable planning permits (TPP) scheme recently discussed in the land use literature in the context of policies aiming to limit land consumption. Furthermore, we relate our estimates to the average municipal costs for land development and execute a number of robustness checks.
Keywords: H21; H25; H70; H71; R14; R52; 330; tax revenues; municipal taxes; land consumption; instrumental variable regression